مطبوعة محاضرات مقياس التيارات الفلسفية والمقاربات العلمية - بن ميصرة ، عبدالرحمان (Mohamed Boudiaf University of M'Sila, 2022)
المدرسي الملخص : بالعربية : تعد وحدة التيارات الفلسفية والمقاربات العلمية مادة دراسية هامة ذات طبيعة معرفية متميزة تقدم معرفة مقررة للطالب، لذلك فإن الاشتغال في البحث والتكوين يستوجب مراعاة تلك الطبيعة من جانبها النظري من جهة وعلاقتها بالواقع المدروس من جهة ثانية. إن دراسة الاتجاهات الفلسفية والمقاربات العلمية تهدف بشكل عام إلى استخلاص رؤية نظرية واضحة المعالم والأبعاد للجوانب التي تشكل المجال المعرفي للمقاربات العلمية التربوية عموما والتربية البدنية والرياضية خصوصا الذي يستلزم تحليل كافة العناصر والمقومات والظواهر الاجتماعية والطبيعية الناتج عن التفكير الدائم والبحث عن الحقائق للوصول الى المعرفة العلمية المطلقة وتحديثها لتوائم متطلبات المجتمعات الإنسانية التي أصبحت التغيير أهم صفاتها. كما تشير الدراسات العلمية الحديثة إلى أن التيارات الفلسفية والمقاربات العلمية النظرية ما هي إلا فلسفة مركبة ترتبط بنظريات وآراء متباينة تسعى لاختيار الأفكار التي تتناسب مع طبيعة أفراد المجتمع التي لا تتنافى مع معتقداته وثقافته والتي تتناسب مع القيم والمبادئ السائدة للمجتمع الجزائري، لأن الحكمة تقتضي أن نتعايش مع الحقائق ولا نتجاهلها ولا نقع في ازدواجية أو تناقض بين ما هو عالمي وبين ما هو محلي عربي إسلامي. Searchlight in English The Automotive philosophy and Scientific Approaches unit is an important study subject with a distinct cognitive nature that provides prescribed knowledge to the student.Therefore, engaing in research and training requires taking into account that nature from its theoretical side on the one hand, and its relationship to the reality studied on the other hand. The studay of philosophical trends and scientific approaches in general leads to the conclusion of a theoretical vision with clear definitions and dimensions of the aspects that constitute the cognitive field of scientific and educational approaches in general and physical and sports education in particular, which requires analysis of all elements, components and social and natural phenomena resulting from constant thinking and searching for facts to reach knowledge and updating it to suit the requirements of human societies, for which change has become its mots important characteristic. Modern scientific studies also indicate that philosophical currents and theoretical scientific approaches are nothing but a complax philosophy linked to disparate theories and opinions that seek to choose ideas that are appropriate to the nature of the members of society, that are not inconsistent with its beliefs and culture, and that are consistent with the prevailing values and principles of Algerian society, because wisdom requires that we coexist. With the facts we do not ignore them, and we do not fall into duality or contradiction between what is global and what is local, Arab-Islamic.
Keywords: التيارات الفلسفية; المقاربات العلمية; الاتجاهات الفلسفية